Cover Image, Volume 77, Issue 9. Issue 9 (16th October 2020) - Taneja, Nilay; Bersi, Matthew R.; Rasmussen, Megan L.; Gama, Vivian; Merryman, W. David; Burnette, Dylan T.
Abstract : ON THE COVER: The cover image © Nilay Taneja and Dylan Burnette] is based on the Original Article Inhibition of focal adhesion kinase increases myofibril viscosity in cardiac myocytes by Nilay Taneja et al., https://doi.org/10.1002/cm.21632 .